Brief Report: Differential Associations of Interleukin 6 and Intestinal Fatty Acid-Binding Protein With Progressive Untreated HIV-1 Infection in Rakai, Uganda. (1st May 2016) - Olwenyi, Omalla A.; Naluyima, Prossy; Cham, Fatim; Quinn, Thomas C.; Serwadda, David; Sewankambo, Nelson K.; Gray, Ronald H.; Sandberg, Johan K.; Michael, Nelson L.; Wabwire-Mangen, Fred; Robb, Merlin L.; Eller, Michael A.
Abstract : Abstract: The significance of HIV-associated immune activation and microbial translocation in Sub-Saharan African population remains poorly defined. We assessed biomarkers of inflammation, microbial translocation, and cellular activation and found most factors elevated in Ugandan HIV-1 seroconverters compared with community-matched controls. In contrast to previous findings in Western cohorts, C-reactive protein, neopterin, and intestinal fatty acid binding protein were not elevated. Higher T-cell activation and IL-6 were associated with faster disease progression. Surprisingly, intestinal fatty acid binding protein, indicative of enterocyte turnover, was higher in slow than in fast progressors. These data suggest differential relationships among biomarkers of intestinal barrier integrity and innate immune activation between developed countries and Sub-Saharan Africa.